The impact of financing constraints on innovation: evidence from small and medium-sized firms in Africa - Carrasco, Isis Amanda Garcia (2022)
Innovation and technological development are in the center of current global discussions. Given the importance of financial support for innovative projects, it is crucial to understand the impact of financial constraints on innovation, mainly in SMEs from emerging economies. This is critical for developing countries, once they can benefit from innovation as a potential driver for economic development and growth. Previous literature focused on cash flow ratio over R&D expenses as a measure for innovation, but more recent studies use new measurement and models. Using the World Bank Enterprise Surveys, and controlling for several firm-level factors, this paper seeks for evidence of the impact of financial obstacles on innovation in East Africa. The Sub-Saharan Africa region presents growth and economic development opportunities, as an area with low levels of industrialization and immense poverty, while the private sector is less developed in that region than in other African countries. Using the logit estimation technique, the study finds that obstacles to access bank credit are a negative force in driving innovation, specifically in Tanzania. For the other countries of the study (Kenya and Uganda), we find no evidence about the impact of credit constraint on innovation. Such evidence indicates that there may be room for improvement in public policies that drive economic growth through financial programs in emerging countries.